REVITALISASI SISTEM PENGELOLAAN SAMPAH TERPADU DI KELURAHAN PUDAKPAYUNG SEMARANG - Samadikun, Budi Prasetyo; Hadiwidodo, Mochtar; Jusihdani, Atiya Nurul (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2016)
This study focused on the existing condition of waste management in Pudakpayung Village Semarang and revitalization efforts on the operational aspects, institutional, and community participation, due to the lack of optimization waste management process in the region. By using the survey method, it is known that the placing and sorting process in existing condition have individual place pattern but have not done the sorting activity which is not entirely discarded inWaste Processing Unit Pudakpayung, with collecting periodization in 2 days and 3 times ritation. Waste Processing Unit Pudakpayung only serve 5 RW in the Pudakpayung Village, and partly Gedawang Village area.